Profit Maximization for Cloud Services in Multiserver Environment - kashypa, Raushan; Sowmya Naik, PT (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing provides resources and services to customers in a dynamic basis. That’s why it has become an effective and very efficient way for computing. Profit plays a very important role from perspective of a cloud service provider. This profit will be determined based on how a cloud service platform has been configured and it also depends on market demand. Generally a single long term renting will be used to configure a cloud platform which is not capable of quality service and it also leads to a greater resource waste.